Effects of land cover, slope, and soil physical properties on runoff coefficient in Upper Brantas Sub-watershed - Cahya, Utik Tri Wulan; Utomo, Wani Hadi; Nugroho, Waego Hadi; Suharyanto, Agus (Journal of Degraded and Mining Lands Management, 2025)
Management of water resources in watersheds requires an in-depth understanding of the factors that influence the runoff coefficient. This study aimed to analyze the influence of land cover, slope, and soil physical properties on the runoff coefficient in the Upper Brantas Sub-watershed and develop a prediction model using multiple linear regression. The research was conducted in Pesanggrahan Village, Batu City, using nine observation plots consisting of three types of land cover (dense canopy, moderate canopy, and sparse canopy) with three slope classes (15%, 25%, and 35%). Surface runoff measurements were conducted using 150 m² plots during the rainy season. Pearson correlation analysis showed that the runoff coefficient was significantly negatively correlated with land cover percentage (r = -0.551; p<0.001) and Dry Microaggregate Ratio (DMR) index (r = -0.439; p<0.001), and significantly positively correlated with slope (r = 0.265; p<0.001) and sand content (r = 0.410; p<0.001). The selected regression model (C = -0.031 - 0.074X1 + 0.015X2 - 0.001X4 + 0.110X6) showed land cover/X1 had the strongest influence (? = -0.074, p<0.0001), followed by slope class/X2 (? = 0.015, p<0.0001), bulk density/X4 (? = 0.110, p<0.001), and silt content/X6 (? = -0.001, p<0.036). The model performed well with a validation R² of 46.3% and a Root Mean Square Error (RMSE) of 0.0331. This research presents a practical model for estimating runoff coefficients, supporting soil and water conservation planning in mountainous areas.